Teacher Learning Innovation to Increase Student Learning Motivation at Muhammadiyah Middle School in Sorong City - Nhindi Sumai; Iriani Suci Kharmillah; Abu Sofyan (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to analyze teachers’ learning innovations in improving students’ learning motivation at SMP Muhammadiyah Kota Sorong. The research employed a qualitative descriptive method with a library research approach. Data were collected from journals, scientific articles, and relevant references discussing innovative learning models, technology-based learning media, and teachers’ strategies in building students’ learning motivation. The findings revealed that the implementation of learning models such as Blended Learning, Project-Based Learning (PjBL), and Flipped Classroom was able to create more active, flexible, and student-centered learning. In addition, the use of interactive media such as Quizizz and animation media made learning more engaging and easier to understand. Humanistic teacher strategies through creating a comfortable classroom atmosphere, providing appreciation, and explaining learning objectives also positively influenced students’ learning motivation.